Estudio de prevalencia de candidiasis oral en pacientes oncológicos adultos bajo quimioterapia que acuden a SOLCA - LOJA en el periodo Septiembre - Diciembre 2022 - González Iñiguez, Jennifer Lizbeth (2023)
Oral candidiasis is one of the most common fungal infections caused by endogenous yeasts, with the yeast Candida albicans being responsible for this condition. It is characterized by the excessive growth of fungi, resulting in white patches on the tongue, throat, and other areas of the oral mucosa, as well as discomfort while swallowing. The incidence of candidiasis is attributed to the development of chronic diseases such as diabetes, cancer, human immunodeficiency virus (HIV), and the use of intensive medications, including antibiotics, chemotherapy, and immunosuppressants. Therefore, the primary aim of this research was to determine the prevalence of oral candidiasis in patients undergoing chemotherapy at the Solca Cancer Institute in the city of Loja. Additionally, the study aimed to investigate the influence of pharmacological dosage and the relationship between chemotherapy treatment and the occurrence of oral candidiasis. An analytical cross-sectional case-control study was conducted involving 16 patients undergoing chemotherapy, with a four-month follow-up period. The study utilized the dental history elaborated and approved for the research project to provide care for patients at the Solca Nucleus Loja between September and December 2022. The obtained results revealed that 50% of the chemotherapy patients in the studied sample exhibited oral candidiasis, amounting to 8 patients. Furthermore, it was determined that there were no significant differences concerning antineoplastic medication, dosage, and chemotherapy relationship in the manifestation of oral candidiasis. In conclusion, it was possible to successfully indicate the presence of oral candidiasis in patients undergoing chemotherapy. However, it remains uncertain whether dosage, medication, and chemotherapy relationship can definitively be linked to changes leading to the development of oral candidiasis